STEM education and school security (2024)
Revamping education sector in Osun State calls for every stakeholder hand to be on deck, especially in fortifying STEM Education for making all available opportunities in this area known. As open systems, the schools have been deeply affected by the economic, political, and social conditions of our time, and have been expose to many undesirable events and behaviours such as substance addiction, violence, child abuse, kidnaping, and the like. Therefore, it is necessary to manage school security properly in order to prevent accidents and incidents, creating an environment in which physical, emotional and social well-being is promoted. This study aimed at examining STEM Education and school security.